2022
DOI: 10.3390/nu14030470
|View full text |Cite
|
Sign up to set email alerts
|

Late-Night Overeating or Low-Quality Food Choices Late at Night Are Associated with Subclinical Vascular Damage in Patients at Increased Cardiovascular Risk

Abstract: Late-night overeating (LNO) is associated with several cardiovascular disease (CVD) risk factors. Limited data exist regarding the association between late-night (LN) systematic food consumption, LNO, and LN poor food quality with subclinical vascular damage (SVD) which precedes the onset of CVD. This study aimed to investigate the above associations with SVD in a large sample of adults, free of established CVD, with one or more CVD risk factors. In total, 901 adults (45.2% males) underwent anthropometric, die… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…In fact, not only the time of eating but also the composition of meal is involved in cardiometabolic damages ( 5 , 197 199 ). In the past decades, studies performed using animal models have revealed that a high-fat diet alters the expression and cycling of circadian clock genes and clock-controlled genes involved in metabolic metabolism in different murine tissues, including the hypothalamus, liver, and adipose tissue ( 200 202 ).…”
Section: When the Orchestra Is Out Of Tune: Circadian Misalignment/de...mentioning
confidence: 99%
“…In fact, not only the time of eating but also the composition of meal is involved in cardiometabolic damages ( 5 , 197 199 ). In the past decades, studies performed using animal models have revealed that a high-fat diet alters the expression and cycling of circadian clock genes and clock-controlled genes involved in metabolic metabolism in different murine tissues, including the hypothalamus, liver, and adipose tissue ( 200 202 ).…”
Section: When the Orchestra Is Out Of Tune: Circadian Misalignment/de...mentioning
confidence: 99%